1967
DOI: 10.1177/004051756703700606
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Solvents on Some Properties of Cotton Cellulose 1

Abstract: Samples of cotton duck were immersed in pyridine, aqueous methylamine solutions, and a variety of other solvents. Pyridine and methylamine caused swelling of the cellulose fibers and an increase in the moisture content of the fabric. Pyridine also increased the fabric breaking strength. This is explained in terms of enhanced plasticization by pyridine and water molecules which are hydrogen-bonded to cellulose. Treatment by pyridine or aqueous methylamine reduced the rate of photochemical degradation of fabric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1968
1968
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…There has been a sustained interest in developing methodologies for multifunctionalization of the Cp ring of ferrocene due to numerous applications of such derivatives in pharmaceuticals, biosensors, and dendrimers as well as in catalysis, electrochemistry, and materials science . Recently, the design and development of ferrocene-based electroactive materials such as semiconductors, conducting polymers, and charge storage materials have been carried out .…”
Section: Introductionmentioning
confidence: 99%
“…There has been a sustained interest in developing methodologies for multifunctionalization of the Cp ring of ferrocene due to numerous applications of such derivatives in pharmaceuticals, biosensors, and dendrimers as well as in catalysis, electrochemistry, and materials science . Recently, the design and development of ferrocene-based electroactive materials such as semiconductors, conducting polymers, and charge storage materials have been carried out .…”
Section: Introductionmentioning
confidence: 99%
“…I It has been generally accepted [6,7,17] that radiation of wavelength greater than 3400 ~ is unable to photolyze pure cell-ulose directly, owing to the lack of light absorption. It has been shown, however, that nonpurified cotton duck is degraded more rapidly in the carbon-arc Weather-Ometer than is the same fabric after rigorous purification [25). In addition, Frampton et al [14] reported a slight but continuous absorption in the 3700-4000 A range by cotton which was apparently not completely free of noncellulosic material.…”
Section: Resultsmentioning
confidence: 99%
“…Part of the noncellulosic material which occurs in 'unpuAfied cotton cellulose can be extracted by methanol and absorbs to a certain extent at wavelengths greater than 3500 A [25]. Other impurities are not soluble in polar solvents and are not removed by scouring and bleaching.…”
Section: Resultsmentioning
confidence: 99%
“…I t lost 607A after leaching for 48 h, but when applied from benzene retained 100% after prolonged leaching. It has also been claimed that pyridine itself exerts a protective action against light [ 4 ] . Benzene was therefore used in the work reported here, but parallel exposures at Didsbury nevertheless gave closely similar results for compounds deposited from pyridine and benzene, respectively, except with the pentachlorophenyl ester (IB), which performed much worse when applied from pyridine.…”
Section: Introductionmentioning
confidence: 99%